2014
DOI: 10.1158/1078-0432.ccr-13-2147
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of the Tumor Mutanome by T Cells during Progression from Primary to Recurrent Ovarian Cancer

Abstract: Purpose: Cancers accumulate mutations over time, each of which brings the potential for recognition by the immune system. We evaluated T-cell recognition of the tumor mutanome in patients with ovarian cancer undergoing standard treatment.Experimental Design: Tumor-associated T cells from 3 patients with ovarian cancer were assessed by ELISPOT for recognition of nonsynonymous mutations identified by whole exome sequencing of autologous tumor. The relative levels of mutations and responding T cells were monitore… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
129
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 143 publications
(134 citation statements)
references
References 76 publications
4
129
0
1
Order By: Relevance
“…Further, the presence of tumor infiltrating lymphocytes (TIL), in particular, CD8 + T cells, has been associated with increased survival (Sato et al 2005;Nelson 2008;Oble et al 2009;Yamada et al 2010;Gooden et al 2011;Hwang et al 2012), suggesting that the adaptive immune system can mount protective anti-tumor responses in many cancer patients (Kim et al 2007;Fox et al 2011). The antigen specificities of tumor-infiltrating T cells remain almost completely undefined (Andersen et al 2012), but there are numerous examples of cytotoxic T cells recognizing single amino acid coding changes originating from somatic tumor mutations (Lennerz et al 2005;Matsushita et al 2012;Heemskerk et al 2013;Lu et al 2013;Robbins et al 2013;van Rooij et al 2013;Wick et al 2014). Thus, the notion that tumor mutations are reservoirs of exploitable neo-antigens remains compelling .…”
Section: [Supplemental Materials Is Available For This Article]mentioning
confidence: 99%
See 1 more Smart Citation
“…Further, the presence of tumor infiltrating lymphocytes (TIL), in particular, CD8 + T cells, has been associated with increased survival (Sato et al 2005;Nelson 2008;Oble et al 2009;Yamada et al 2010;Gooden et al 2011;Hwang et al 2012), suggesting that the adaptive immune system can mount protective anti-tumor responses in many cancer patients (Kim et al 2007;Fox et al 2011). The antigen specificities of tumor-infiltrating T cells remain almost completely undefined (Andersen et al 2012), but there are numerous examples of cytotoxic T cells recognizing single amino acid coding changes originating from somatic tumor mutations (Lennerz et al 2005;Matsushita et al 2012;Heemskerk et al 2013;Lu et al 2013;Robbins et al 2013;van Rooij et al 2013;Wick et al 2014). Thus, the notion that tumor mutations are reservoirs of exploitable neo-antigens remains compelling .…”
Section: [Supplemental Materials Is Available For This Article]mentioning
confidence: 99%
“…2013; Robbins et al 2013;van Rooij et al 2013;Wick et al 2014). However, from these investigations it appears that missense mutations with demonstrable endogenous immunoreactivity are relatively rare.…”
Section: à3mentioning
confidence: 99%
“…For example, in anecdotal studies of melanoma patients who responded well to TIL therapy or ipilimumab, TIL were shown to recognize only about 2% of mutations identified by whole exome sequencing (8,9,38). Similarly, in a study of three ovarian cancer patients, we found that TIL recognized only 1.3% (1/78) of mutations (11). Finally, in a non-small cell lung cancer patient who responded to pembrolizumab, only one mutation was recognized out of 226 putative neoantigens (39).…”
Section: Discussionmentioning
confidence: 68%
“…First, for a given mutation to be recognized by the immune system, several criteria must be met: (i) a peptide containing the mutant residue must be generated by the antigen processing machinery; (ii) the mutant peptide must bind with sufficient affinity to one or more of the patient's HLA alleles; and (iii) the patient must harbor T cells that recognize the mutant peptide-HLA complex (7). Owing to these factors, studies in melanoma and other cancers have found that only about 0.5%-4% of nonsynonymous mutations spontaneously trigger T-cell recognition (8)(9)(10)(11). A second major issue is immune editing, whereby the immune system eliminates cells expressing specific antigens (12).…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12][13][14] Nonetheless, neoplastic cells often express a set of polypeptides that differs from that of their normal counterparts and, at least theoretically, can be harnessed to elicit a relatively specific immune response. [15][16][17][18][19][20][21] The peculiar antigenic profile of cancer cells reflects (1) malignant transformation itself, which is normally associated with primary genetic and epigenetic changes that not only can result in the synthesis of mutant/fusion proteins, but also influence gene expression at a global level; [22][23][24][25] (2) genetic/ genomic instability, i.e., the tendency of neoplastic cells to accumulate additional genetic changes (be them punctual or of higher magnitude), further increasing the amount of potentially immunogenic polypeptides; [26][27][28][29][30] (3) intracellular and microenvironmental factors that promote adaptive responses linked to changes in protein translation and proteasomal degradation, and hence directly affecting the so-called immunopeptidome, i.e., the set of peptides presented on the cell surface in complex with MHC molecules. [31][32][33] Thus, malignant cells near-to-invariably express so-called "tumor-associated antigens" (TAAs), i.e., antigens that qualitatively or quantitatively differ from those expressed by normal cells of the same type.…”
Section: Introductionmentioning
confidence: 99%